Islam Relation in The Iban and Malay Communities in Jongkong Kapuas Hulu - Aripin, Zainal (The Pontianak State Institute of Islamic Studies, 2018)
This article discusses the position of Islam in the interaction between Iban and Malays in Jongkong, Kapuas Hulu. So far, people often place the position of Iban people as Dayaks, which in fact is in opposition to Malay and Islam. Islam is considered unfriendly to the Dayaks and has become a stigma reinforced by various actual events in West Kalimantan and in Indonesia. Data collected in the field in Jongkong and Pengerak, were obtained through interviews and observations and literature studies, the data shows that the relationship between Iban and Malays in Jongkong is very close. Interaction has been established for a long time, and Islam is present in that relationship through Malays and through Ibans who embrace Islam, through economic and educational activities. This relationship is so close that Iban non-Muslims are willing to go to the Jongkong Islamic School. In part, Iban youths are offered to marry Malays. This relationship can be a model for realizing a harmonious life.